The development of techniques for assessing compactibility of field soils. - Alexandrou, Athanassios (Cranfield University, 1995)
During the last five decades, effects of soil compaction on crop growth and yield have been of increasing concern due to the introduction of heavier agricultural machinery. Most researchers agree that, although a certain degree of compaction can be beneficial to crops, loading beyond this can be very detrimental and, therefore, soil compaction should be considered as an important factor which should be managed in crop production systems. The majority of work to date has been conducted using disturbed soil samples and hence not representative of field situations. The aim of this project was to investigate further the compactibility behaviour of field soils. Work was conducted in a soil bin as well as on field soils (sandy loam and clay ) in a range of climatic conditions. Techniques for assessing soil compactibility are proposed, based on the stress-strain (load-sinkage) characteristics of soil, soil strength prior to loading, and the mode and extent of soil deformation for a given loading situation. The determination of these soil characteristics proved somewhat cumbersome and time consuming and, therefore, the prediction of these variables from more easily determined soil properties (volumetric water content, initial dry bulk density, void ratio and degree of saturation) was investigated with promising results. In addition, a model is proposed which predicts the extent of deformation within the soil profile for a given loading situation.